Austral Flamingo Phoenicopterus chilensis Sustaining an Injury Derived from Recreational Fishing Gear - Beron, Maria Paula (2019)
Abandoned, lost and discarded fishing gear in coastal environments has become a growing concern. Countless species of waterbirds and seabirds that are found regularly along the coasts are threatened by monofilament lines that are lost (with or without hooks) or are discarded along resting areas. Fishing gear injuries, such as swallowed hooks and constriction wounds from line entanglement, are common in many birds. Here I report an injured individual of the Austral Flamingo (Phoenicopterus chilensis) in southeastern of Buenos Aires Province, Argentina. This constitutes the first report of this specie with fishing gear injury. Actually P. chilensis is listed as Near Threatened because it is suspected that it will undergo a moderately rapid population decline over the next three generations due, among other, to disturbance and the degradation of its habitat. Future research should include conducting a survey on abandoned, lost and discarded fishing gear given the threat they represent to the local wildlife and potentially coastal users. Particularly in species that use areas with strong anthropic pressure, species with compromised conservation states or charismatic such as P. chilensis.